A synergetic model for implementing single-component white-light emission: a case study of zero-dimensional cadmium halides. (18th January 2023) - Yuan, Jiantao; Zhou, Guojun; Zhang, Jian; Zhang, Xian-Ming
Abstract : A serial of 0D (C6 H7 NX)2 CdX4 (X = Cl, Br, I) are developed, and the synergetic controlling of π-conjugated ligands and [CdX4 ] units enables single-component ultra-broadband white-light emissions of (C6 H7 NCl)2 CdCl4 and (C6 H7 NBr)2 CdBr4 . Abstract : Although low-dimensional hybrid metal halides have recently been the subject of considerable attention as white-light emitters, the superiority of structural diversity has not been relied upon to tune photoluminescence (PL) behaviors by synergistic control of organic and inorganic compositions. Herein, a series of distinctive cadmium halides (C6 H7 NX)2 CdX4 (X = Cl, Br, I) with π-conjugated ligands and halogen substitution are developed, in which the isolated [CdX4 ] 2− tetrahedrons are separated by large [C6 H7 NX] + organic cations into a unique zero-dimensional (0D) host-guest structure. Intriguingly, the synergetic controlling of π-conjugated ligands and [CdX4 ] 2− units enables single-component ultra-broadband white-light emissions with a record color rendering index (CRI) of 99 in the above novel 0D cadmium halides. (C6 H7 NCl)2 CdCl4 and (C6 H7 NBr)2 CdBr4 exhibit ultra-broadband cold white-light emission with large full-width at half-maximum (FWHM) of 218 nm and 244 nm, respectively, which is triggered by the synergistic emissions of [C6 H7 NX] + ligands and self-trapped excitons (STEs) of Cd 2+ . A comparison of PL properties of cadmium halides with Cl/Br/I transmutation elucidated that the nature of the halogens is strongly dependent on the trapping/de-trapping of STEs as well as on the π → π* transition of the π-conjugated ligands, along with the resulting PL modulation on emission intensities, wavelengths, and FWHM. This work reveals a unique synergetic model for implementing white-light emission and extends to the design of high-performance hybrid emitters.